Spatio-Temporal Evolution Model of the Hydraulic Transport Characteristics of Particulate Solids - Zhang, Zhi; Sun, Baojiang; Wang, Zhiyuan; Pan, Shaowei; Lou, Wenqiang; Tong, Shikun (Frontiers in Earth Science, 2021)
The hydraulic transport of solid materials is widely used in various industrial fields owing to its high efficiency, low cost, and environmental friendliness, and it has received extensive attention. However, the violent interaction between the liquid and solid phases during transportation makes the slurry flow strongly unsteady and heterogeneous, and it is difficult to use the existing mathematical models describing the motion characteristics in the hydraulic transport of slurry because of the limitations of a single theory or experimental data basis. In this study, considering the randomness and uncertainty in the transportation of solids, a spatio-temporal evolution model of the hydraulic transport characteristics of particulate solids was established. This model is suitable for hydraulic transport in pressure pipelines and open channels, and it can be used to analyze the influence of changes in the motion and property parameters of the liquid–solid phase on the characteristics of the temporal-spatial evolution of the slurry velocity and concentration distributions. The rationality of the model was verified through laboratory experiments. Through an interaction analysis of slurry components, this work explores the influence of the transport of solids on the slurry motion and property parameters, fills the gap in the evolution mechanism of the slurry velocity and concentration distributions in existing models, and overcomes the limitation that layer-based models can only be used in pressure pipelines. Therefore, it has important guiding significance for the engineering design of particulate solid hydraulic transport.